Implementasi Agile Model Pada Perancangan Aplikasi Urunan Dana Berbasis Android di Lembaga Semangat Bantu - Fadillah Fahruddin; Aries Saifudin (CV. Multi Kreasi Media, 2023)
Currently, online fundraising can almost be done easily, one of which is through a website. Fundraising through the Semangat Bantu website, which started in 2020, has been going well, from the data recorded so far, 97.5% of visitors are Android users and with the current state of the website, donors are always asked to fill in their data when they want to donate. will slow down the flow of donations, allowing the donor to discontinue the donation. Seeing the advancement of technology with the increase in Android users, an Android application was made. Agile Development with the scrum development method is an option that is needed at this time to develop an application that allows easy flexibility and development that tends to be shorter without reducing the quality of application functions. From the results of the android application that was built using the scrum method with the current function, namely that donors only need to register once, they can donate more without having to fill in personal data, it can speed up the flow of donation transactions at the Semangat Bantu institution and by choosing the suitable development method this application is handy easy to maintain and in the future, it will be effortless if development is done.